β1-Integrin plays a major role in resveratrol-mediated anti-invasion effects in the CRC microenvironment - Aranka Brockmueller; Anna-Lena Mueller; Parviz Shayan; Mehdi Shakibaei (Frontiers in Pharmacology, 2022)
Graphical Abstract